Exploitation of bacteria from forest ecosystem for antimicrobial compounds - Saravanan D, S. Bharathi, M. Radhakrishnan, R. Balagurunathan (Journal of Applied Pharmaceutical Science)
This study deals with bacterial prospecting from forest soil with special reference to antimicrobial substances. Total of 25 morphologically different bacterial colonies were isolated from soil samples collected from Anaimalai forest and Parambikulam tiger reserve forest, Western Ghats, India. About 12 (48%) out of 25 isolates showed antibacterial activity in which strain AF1 showed inhibitory activity against more number of test pathogens. Bioactive substance from strain AF1 was produced by adopting submerged fermentation and extracted using ethyl acetate and chloroform. In disc diffusion method, ethyl acetate extract showed good antibacterial activity (9-17 mm zone of inhibition). Active fraction present in the ethyl acetate extract was determined by thin layer chromatography based bioautography. Findings of this work supported that the forest ecosystems investigated in this study will be potential place for bacterial bioprospecting.
Keywords: Western Ghats,bacteria,antimicrobial activity,bioautography.